The Effect Of The Savi Learning Model In Improving Mathematical Problem Solving Abilities In Elementary School Students - Retnowati, Evi; Usodo, Budi; Chumdari, Chumdari (Jurnal Ilmu Sosial Mamangan, 2025)
This study aims to examine the effect of the SAVI (Somatic, Auditory, Visual, and Intellectual) learning model on the problem-solving abilities in mathematics of fifth-grade students at SDN Gugus Sukorejo, Kebonsari, Madiun. The method used in this research is a quasi-experimental design with a pretest-posttest control group. The sample consists of two classes: an experimental class implementing the SAVI model and a control class using conventional teaching methods. Data were collected through problem-solving ability tests administered before and after the learning process, as well as observations during the learning activities.The results indicate that the SAVI learning model is effective and significantly influences the improvement of problem-solving abilities in mathematics among fifth-grade students at SDN Gugus Sukorejo, Kebonsari, Madiun. The total score for SAVI (P0) reached 2,848.31 with an average of 949.44, significantly higher than the total score for the Conventional method (P1), which was only 900.32 with an average of 300.11. Students in the high-ability group using SAVI achieved a score of 1,045.35, more than double that of the high-ability group using the Conventional method (405.82). The SAVI model also demonstrated better results in the medium and low ability groups, indicating its effectiveness across all ability categories. The significant score difference in SAVI (1,045.35 vs. 815.67) reflects an improvement in student understanding. These findings affirm that the SAVI model is more effective than conventional methods in mathematics education.